Diagnostic approach and management of genetic aortopathies. (February 2020) - Bhandari, Rohan; Aatre, Rajani D; Kanthi, Yogendra
Aortic aneurysms were the primary cause of nearly 10, 000 deaths in 2014 according to data from the Centers for Disease Control and may involve segments of the thoracic or abdominal aorta. Thoracic aortic aneurysms and dissections are more commonly associated with an underlying genetic etiology. In the past several decades, in parallel with the burst of new genome sequencing technologies, a number of genetic aortopathies have been identified. These have provided important insights into the molecular mechanisms of aneurysmal disease, but pose challenges in clinical practice as there are limited consensus recommendations at this time. In this review, we aim to address the pathophysiology, clinical presentation, and treatment considerations in the key heritable thoracic aortopathies.